1982
DOI: 10.1042/bj2020333
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-mediated insulin degradation and insulin-stimulated glycogenesis in cultured foetal hepatocytes

Abstract: Insulin-stimulated glycogenesis and insulin degradation were studied simultaneously at 37 degrees C in cultured foetal hepatocytes grown for 2-3 days in the presence of cortisol. Degradation of cell-associated insulin, as measured by trichloroacetic acid precipitation, was significant after 4 min in the presence of 1-3 nM-125I-labelled insulin. This process became maximal (30% of insulin degraded) after 20 min, a time when binding-state conditions were achieved. No insulin-degradative activity was detected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
1
1

Year Published

1982
1982
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 46 publications
5
32
1
1
Order By: Relevance
“…Although it is a matter of some debate whether peptide hormone metabolism plays a role in the mechanism of hormone action (32)(33)(34), it is at least clear that hormone metabolism by target tissues is a function, in large part, of ligand interaction with plasma membrane receptors and that it occurs in parallel with processes by which hormone-receptor interactions regulate cellular events (3)(4)(5)(6)16). By use of isolated hepatocytes, we have demonstrated that (a) a major peptide product of glucagon metabolism is glucagon(4-29), (b) the hormone fragment, rather than being stored or further degraded, is released into the cell incubation medium, and (c) the fragment arises from cell-mediated processes that require components in addition to highly purified plasma membranes per se.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is a matter of some debate whether peptide hormone metabolism plays a role in the mechanism of hormone action (32)(33)(34), it is at least clear that hormone metabolism by target tissues is a function, in large part, of ligand interaction with plasma membrane receptors and that it occurs in parallel with processes by which hormone-receptor interactions regulate cellular events (3)(4)(5)(6)16). By use of isolated hepatocytes, we have demonstrated that (a) a major peptide product of glucagon metabolism is glucagon(4-29), (b) the hormone fragment, rather than being stored or further degraded, is released into the cell incubation medium, and (c) the fragment arises from cell-mediated processes that require components in addition to highly purified plasma membranes per se.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that the increase in insulin binding in the presence of chloroquine is due to the decrease in insulin degradation by the inhibition of lysosomal function (Marshall and Olefsky, 1979, Kobayashi et al, 1980, and Plas and Desbuquois, 1982. However, it was demonstrated that IM-9 lymphocytes lost receptor-mediated insulin degrading activity and that chloroquine did not decrease the insulin degradation (Baldwin et al , 1980, Misbin et al , 1980, Sonne and Gliemann, 1980, Saviolakis et al, 1981, and Iwamoto, et al, 1981.…”
Section: Discussionmentioning
confidence: 99%
“…Chloroquine, a lysosomotropic agent, increases cell-associated insulin, and decreases receptor-mediated insulin degradation in adipocytes Olefsky, 1979, Kobayashi et al 1980) and hepatocytes (Plas and Desbuquois, 1982). It has been hypothesized that the increase in insulin binding in the presence of chloroquine is due to the decrease in insulin degradation by the inhibition of lysosomal function (Marshall and Olefsky, 1979, Kobayashi et al, 1980, and Plas and Desbuquois, 1982.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Le phénomène de diminution du nombre de récepteurs de l'insuline après exposition prolongée à l'hormone (« down regulation ») décrit dans les hépatocytes adultes en culture primaire (Blackard, Guzelian et Small, 1978 ;Caro et Amatruda, 1980) n'est pas détecta-ble dans les hépatocytes foetaux j menuelle et Plas, 19811. En présence de chloroquine qui modifie le devenir du complexe insuline-récepteur dans la cellule, on observe une perte spécifique de l'effet glycogénique de l'insuline sans modification de l'effet glycogénique d'une charge de glucose (Plas et Desbuquois, 1982). Cette drogue révèle donc une situation analogue à celle obtenue dans les hépa-tocytes désensibilisés à l'hormone.…”
Section: Introductionunclassified